The effect of trick intervention 20-20-20 on computer vision syndrome incidence in computer workers - Putri Anggrainy; Rodiah Rahmawaty Lubis; Taufik Ashar (Ukrainian Journal of Ophthalmology, 2025)
Computer Vision Syndrome is a collection of symptoms that occur due to overwork with computers, including laptops, desktops, tablets and other display devices (such as smartphones and other electronic reading devices). Resting your eyes continuously and regularly has a huge effect in overcoming the syndrome. The purpose of this study was to analyze the effect of trick intervention 20-20-20 on the incidence of computervision syndrome in computer workers. The research method used is Quasi Experimental Design with the form of Nonequivalent Control Group Design. The total sample of this study was 76 people divided into two groups, namely the intervention and control groups. The samples in each group amounted to 38 people obtained by purposive sampling. Bivariate analysis used the Wilcoxon test for paired samples and the Mann-Whitney test for unpaired samples with a significance level of 95% (? = 0.05). The results of statistical tests in the intervention group showed significant differences in the score of computer vision syndrome between before and after the intervention (? <0.05). The results of statistical tests between the intervention and control groups also showed a significant difference in the incidence of computer vision syndrome between the intervention and control groups (? <0.05). The conclusion in this study was that there was a significant effect of trick intervention 20-20-20 on the incidence of computer vision syndrome in respondents.